1995
DOI: 10.1108/eb021011
|View full text |Cite
|
Sign up to set email alerts
|

The New Engineering Contract: principles of design and risk allocation

Abstract: The paper begins with a brief history of the New Engineering Contract (NEC) and outlines the response by the NEC Panel to the proposals made in the Latham Report. The main principles adopted for the design of the contract are described and the main procedures which are used to implement the design principles are outlined. Emphasis is given to the way in which the procedures are intended to stimulate good management of contracts. The final section of the paper deals with risk allocation and management in NEC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…Previous overseas literature has revealed that guaranteed maximum price (GMP) and target cost contracting (TCC) procurement strategies can accrue a plethora of mutual benefits to all of the parties involved, provided they are properly structured, implemented and managed (Trench, 1991;Walker et al, 2000). The New Engineering Contract which includes various target cost contract options has been adopted in the engineering and construction sectors throughout the United Kingdom and overseas for several years (Broome and Perry, 1995;Perry, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous overseas literature has revealed that guaranteed maximum price (GMP) and target cost contracting (TCC) procurement strategies can accrue a plethora of mutual benefits to all of the parties involved, provided they are properly structured, implemented and managed (Trench, 1991;Walker et al, 2000). The New Engineering Contract which includes various target cost contract options has been adopted in the engineering and construction sectors throughout the United Kingdom and overseas for several years (Broome and Perry, 1995;Perry, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Cornes (1996) contends that use of plain language could blur legal certainty. Perry (1995) observes that it can cause lack of precision and legal scrutiny required for a legal document. Plain language can bore people and make them lose the significance of a clause (Broome & Hayes, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A good move in this regard could be observed in the increased readability levels of the NEC/ECC contract clauses (Perry 1995;Broome & Hayes 1997;Rameezdeen & Rajapakse 2007). NEC is a standard contract specifically developed with a focus on reducing legalese and the drafting of plain easy to read language structure.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca kullanılan standart dokümanlar, mal sahibi açısın-dan yüklenicilerden gelen tekliflerin karşılaştırılması ve değerlendirilmesi için ortak bir temel sağlamaktadır (Rhys Jones, 1994). Mal sahibi ve yüklenici standart dokümanlar kullanarak, sözleşmenin hazırlanması sırasında proje ile ilgili kritik konular ve tarihler nedeniyle gözden kaçabilecek riskleri azaltıp, bu risklerin yönetme fırsatına sahip olurlar (Perry, 1995). Standart sözleşme dokümanlarının kullanımı sayesinde sözleşmede yer alan hükümler, sözleşmenin tarafları tarafından açık ve net bir şekilde anlaşılmakta, özel-likle de anlaşmazlıkların çözümlenmesinde yer alan yön-temler ve prosedürler detaylı bir şekilde tanımlanmaktadır (Broome ve Hayes, 1997;Rameezdeen ve Rajapakse, 2007;Smith, 2008).…”
Section: Standart Sözleşme Dokümanlarıunclassified